The Comprehensive Systematic Review of Association of PSA Level to Clinical Stage of Carcinoma Prostat - Brahm Setioesa; Bendy Dwi Irawan; Cita Pakarti Dharma Kusuma (The International Journal of Medical Science and Health Research, 2026)
Introduction: Prostate-specific antigen (PSA) is a cornerstone biomarker in prostate cancer (PCa) management, used for screening, diagnosis, staging, and monitoring treatment response. However, the precise relationship between PSA levels and clinical stage is complex and influenced by numerous factors. This systematic review synthesizes the current evidence to elucidate the association between PSA and the clinical stage of prostate carcinoma. Methods: A comprehensive systematic review was conducted. We screened studies based on predefined criteria, including the involvement of prostate cancer patients, measurement of serum PSA levels, availability of clinical staging information, and analysis of the PSA-stage relationship. Studies were limited to human clinical studies with adequate sample sizes (≥10 patients) that examined pre-treatment PSA. Data were extracted on study design, patient characteristics, PSA measurement details, staging systems, statistical analyses, primary findings, outcomes, confounding variables, and study quality from 80 included sources. Results: The evidence demonstrates a significant but nuanced association between PSA levels and clinical stage. Established PSA thresholds correlate with disease severity: levels <10 ng/mL are typically linked to localized disease (T1-T2), while levels >20 ng/mL consistently predict advanced/high-risk or metastatic disease (Buzzoni et al., 2015; Tombal et al., 2010). However, paradoxical findings exist, such as worse survival in high-grade patients with very low PSA (<4.0 ng/mL), indicating aggressive tumor biology with reduced PSA secretion (Kang et al., 2020). PSA kinetics (doubling time, nadir) and density (PSAD) provide enhanced prognostic value beyond absolute PSA levels. For instance, a PSA nadir <0.2 ng/mL post-treatment is strongly associated with superior overall survival (Harshman et al., 2017; Tripathi et al., 2025). The relationship is modified by tumor grade, prostate volume, race, and treatment modality. Multi-kallikrein panels improve predictive accuracy over PSA alone (Vickers et al., 2010). Discussion: The PSA-stage relationship is context-dependent. PSA serves as a robust but imperfect predictor. Its utility is maximized when integrated with other parameters like Gleason score, imaging, and kinetics. The "PSA pyramid" concept allows for individualized screening intervals based on baseline PSA (Randazzo et al., 2015). Treatment decisions, such as radiation dose escalation or ADT duration, can be effectively guided by specific PSA thresholds and nadir values (Al-Mamgani et al., 2010; Ayoub et al., 2022). Conclusion: PSA levels are strongly associated with the clinical stage of prostate carcinoma, providing critical prognostic information. However, interpretation must account for modifying factors like tumor grade and prostate volume. Future management should emphasize a multiparametric approach, combining PSA with advanced biomarkers and imaging for precise risk stratification and personalized treatment planning.